Method for assisting in recycling positive electrode material of waste lithium ion battery by siderite
By adopting siderite auxiliary treatment method when recycling the positive electrode material of waste lithium-ion batteries, the problem of difficulty in controlling pyrite activation and iron phase homogenization in the prior art is solved, and efficient lithium extraction and nickel-cobalt alloy are realized. Excellent electrocatalytic performance.
Patent Information
- Application Number
- CN202411493528.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, when recycling the cathode material of waste lithium-ion batteries, pyrite needs to be activated, and the treated iron phase is difficult to homogenize and control, resulting in poor separation and resource utilization of components such as iron, cobalt, nickel and other components.
The method of siderite assisted recycling of the positive electrode material of waste lithium-ion batteries is adopted. By mixing the waste positive electrode material with siderite, transforming at a temperature of 300-700℃, and then water-soaking to obtain lithium liquid and transformation slag. This process does not require activation of siderite, which can effectively catalyze the destruction of the crystal structure of the positive electrode material and highly selectively convert it into α-Fe2O3 phase material, which is conducive to the efficient separation and resource utilization of components.
It realizes efficient extraction and recovery of lithium, and optimizes the particle size and physicochemical characteristics of nickel-cobalt alloy, so that it takes into account excellent electrocatalytic hydrogen production activity, while improving the purity and separation effect of α-Fe2O3 phase materials.
Smart Images

Figure CN119390130A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery waste recycling, and specifically relates to the field of waste lithium battery material recycling. Background Art
[0002] The resource and environmental issues brought about by the large-scale production and utilization of lithium-ion batteries cannot be ignored. On the one hand, the reserves of several metal resources mainly involved in lithium-ion batteries are limited, and there are huge differences in the distribution of key elements on the earth. Continuing to develop new resources on the earth will not lead to the sustainable development of lithium-ion batteries. On the other hand, a large number of retired batteries need to be properly stored and handled, otherwise the heavy metals, lithium salts, organic solvents and other harmful substances in the waste batteries will pollute the soil and water, threatening human health.
[0003] Pyrometallurgy is the main means of large-scale recovery of positive electrode materials. The prior art has also reported some related technical means. For example, the Chinese patent document with publication number CN115652082A discloses a FeS2-assisted spheroidization-oxidation roasting method for lithium extraction of waste positive electrode materials, which specifically discloses that the waste positive electrode materials, FeS2 source, ball-forming binder, and solvent are spheroidized in a ball-forming machine to obtain green balls; the green balls are roasted in an oxygen-containing atmosphere to obtain a roasted material, and the roasted material is water-immersed to obtain a lithium extraction solution and a transition metal slag; the temperature of the roasting stage is 200-300°C; the solvent is an alcohol-containing aqueous solution, wherein the volume content of the alcohol is 20-70v%.
[0004] For another example, the Chinese patent document with publication number CN117613438A discloses a method for recycling and reusing waste ternary lithium-ion batteries, specifically recording a scheme of using pyrite ball milling activation to participate in the recovery of positive electrode materials. For another example, the Chinese patent document with publication number CN116970811A discloses a synchronous recovery process for lithium, manganese, nickel and cobalt in the positive electrode materials of waste ternary lithium batteries, specifically recording a scheme of using calcium chloride and ferrous sulfide to participate in the recovery of positive electrode materials.
[0005] In summary, the prior art also involves some processes that use iron ore to participate in the recovery of waste positive electrode materials, but most of the iron-containing minerals in the prior art need to be activated by means of granulation, ball milling and the like, and the recovered iron materials are difficult to recycle. Summary of the invention
[0006] In view of the problems faced by the existing recycling of positive electrodes of waste lithium-ion batteries, the purpose of the present invention is to provide a method for recycling positive electrode materials of waste lithium-ion batteries with the assistance of siderite, aiming to improve the recycling and resource recovery effect of waste positive electrode materials based on a new idea.
[0007] The prior art reports some recycling processes based on pyrite participating in waste positive electrode materials. The process uses the sulfur behavior of pyrite under oxygen-containing conditions to treat waste positive electrode materials. Most of these processes require activation of pyrite, and the physical phase of the treated iron is difficult to homogenize and control, which will further increase the separation and resource utilization of components such as iron, cobalt, and nickel. In response to this problem, the present invention has conducted in-depth research and provided the following new means:
[0008] A method for recycling waste lithium-ion battery positive electrode materials with the aid of siderite, comprising: mixing waste positive electrode materials stripped from waste lithium-ion batteries with siderite, transforming at a temperature of 300-700°C, and then immersing in water to obtain lithium liquid and transformation slag.
[0009] The present invention innovatively uses siderite to assist in the treatment of waste positive electrode materials, so that the crystal structure of the active material in the waste positive electrode materials can be effectively catalytically destroyed without activation. In addition, the iron can be highly selectively converted into α-Fe2O3 phase material under the combined action of the process and the positive electrode material, which is conducive to its efficient separation from other components and resource utilization.
[0010] In the present invention, the positive electrode active material contained in the waste positive electrode material is an oxidized lithium salt of at least one element among nickel, cobalt and manganese; preferably at least one of lithium cobaltate, lithium nickelate, nickel-cobalt binary material and nickel-cobalt-manganese ternary material; further, it can be at least one of nickel-cobalt binary material and nickel-cobalt-manganese ternary material.
[0011] The present invention shows that the combined transformation of siderite and waste cathode materials can effectively destroy the lattice of the cathode material. In addition, it is also beneficial to obtain nickel-cobalt electrocatalytic materials and α-Fe2O3 phase materials with high electrocatalytic activity.
[0012] In the present invention, the waste positive electrode material is also allowed to contain a conductive agent; preferably, the conductive agent includes at least one of conductive carbon black, graphite, and graphene.
[0013] In addition, the waste positive electrode material is also allowed to contain components such as a binder present in the waste positive electrode.
[0014] In the present invention, in the waste positive electrode material, the content of positive electrode active material is 70-90wt.%, and the content of conductive agent is 5-15wt.%.
[0015] In the present invention, the weight ratio of the waste positive electrode material to the siderite is 1:2-10, preferably 1:3-7.
[0016] In the present invention, the protective atmosphere is at least one of nitrogen and inert gas.
[0017] In the present invention, the transformation process includes a first heat preservation process at a temperature of 300 to 400°C and a second heat preservation process at a temperature of 500 to 600°C. In the present invention, the waste positive electrode material and siderite are heated to the transformation temperature in a protective atmosphere and are kept warm for transformation. Studies have shown that based on the two-stage transformation treatment and temperature control, the lithium extraction effect can be further optimized. In addition, the electrocatalytic activity of the obtained material and the purity of the α-Fe2O3 phase can also be further optimized.
[0018] In the present invention, the holding time at the transition temperature is 30 to 90 minutes. When the preferred two-stage transition process is selected, the first stage transition time can be 10 to 30 minutes; the second stage transition time can be 30 to 60 minutes.
[0019] In the present invention, the liquid-to-solid ratio in the water immersion stage is 5 to 30 ml / g.
[0020] Preferably, the hydrolysis temperature is 15-45°C.
[0021] Preferably, the immersion time is 0.5 to 3 hours.
[0022] In the present invention, when the waste positive electrode material is a nickel-cobalt-containing material, it is subjected to the transformation and water immersion treatment, and then the water immersion residue is subjected to magnetic separation treatment to obtain magnetic separation material and magnetic separation residue; the magnetic separation material is used as a catalyst for electrocatalytic hydrogen production.
[0023] The research of the present invention shows that the process can realize the efficient extraction and recovery of lithium. In addition, the particle size and physical and chemical characteristics of the obtained nickel-cobalt alloy can be optimized so that it can have excellent electrocatalytic hydrogen production activity.
[0024] In the present invention, more than 95% of the iron in the magnetic separation slag is in the form of α-Fe2O3.
[0025] Beneficial Effects
[0026] The present invention innovatively uses siderite to participate in the transformation of waste positive electrode materials, which can effectively destroy the lattice of the positive electrode material, thereby achieving efficient pre-extraction of lithium. In addition, high-performance electrocatalytic materials can be co-produced. Moreover, the siderite can obtain α-Fe2O3 phase materials with high selectivity, which is conducive to its efficient separation from other components and resource utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the XRD diagram of the magnetic separation slag prepared in Example 1. DETAILED DESCRIPTION
[0028] The present invention will be further described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0029] In the present invention, the waste lithium-ion battery positive electrode material is a material obtained by peeling and drying the positive electrode sheet of the waste positive electrode material in NMP solvent, wherein the content of the positive electrode active material can be 80-85wt.%, and the content of the conductive carbon black is 8-12wt.%. In addition, some binders, positive electrode current collectors and other components are also allowed to exist.
[0030] Example 1
[0031] Step 1:
[0032] The waste positive electrode material (in this case, the waste nickel-cobalt binary positive electrode material, that is, the positive electrode active material is a binary material with a nickel-cobalt molar ratio of 1 to 5:1) and siderite are mixed evenly in a mass ratio of 1:5, and the mixture is placed in a tubular furnace, argon gas is introduced, and then the temperature is increased to 500°C at a rate of 10°C / min and kept at this temperature for 60 minutes; then the mixture is cooled with the furnace to obtain a calcined material;
[0033] Step 2:
[0034] The roasted material was treated with water leaching, wherein the liquid-to-solid ratio was 20 ml / g, the water leaching temperature was 20-30° C., and the water leaching time was 1 hour; then the solid-liquid was separated to obtain lithium liquid and water leaching residue; the leaching rate of Li in the leaching solution was 99.3%.
[0035] Step 3:
[0036] The water-leached residue and the dried residue are subjected to magnetic separation treatment to obtain nickel-cobalt material (magnetic separation material) and magnetic separation residue; the magnetic separation residue is subjected to XRD testing, and the results are as follows Figure 1 As shown, it is α-Fe2O3. The metal recovery rate of the magnetic separation material (referring to the recovery rate of nickel and cobalt elements in the positive electrode material) is 95.3%.
[0037] The H2O2 yield of the magnetically separated NiCo alloy was further evaluated in an electrochemical H-type cell under 1 M KOH conditions. After electrolysis at 0.6 V for 100 h, the NiCo alloy showed stable operation with negligible current drop, a high Faradaic efficiency of 88%, and a H2O2 yield of 320 mmol g-1h-1, maintaining a high H2O2 generation selectivity of more than 85%.
[0038] Example 2
[0039] Compared with Example 1, the only difference is that the waste positive electrode material is changed to waste NCM ternary material, in which the active material is NCM, and the molar ratio of the three is 1:1:1; other operations and parameters are the same as Example 1.
[0040] Among them, the leaching rate of Li in step 2 is 99.3%.
[0041] The obtained magnetic separation material has a Faraday efficiency of up to 89%, a H2O2 yield of 325 mmol g-1h-1, and maintains a high H2O2 generation selectivity of over 87%.
[0042] Example 3
[0043] Compared with Example 1, the only difference is that the mass ratio of the waste positive electrode material to the siderite is changed. The experimental groups are:
[0044] Group A: The weight ratio of waste positive electrode material and siderite is 1:7.
[0045] Group B: The weight ratio of waste positive electrode material and siderite is 1:3.
[0046] The test was carried out according to the method of Example 1, and the results were:
[0047] Group A: The leaching rate of Li in step 2 was 99.6%. The Faraday efficiency of the magnetic separation material was as high as 90%, the H2O2 yield was 330mmol g-1h-1, and the high H2O2 generation selectivity of more than 88% was maintained.
[0048] Group B: The leaching rate of Li in step 2 was 99.1%. The Faraday efficiency of the magnetic separation material was as high as 83%, the H2O2 yield was 316mmol g-1h-1, and the high H2O2 generation selectivity of more than 83% was maintained.
[0049] Example 4
[0050] Compared with Example 1, the only difference is that the roasting conditions in step 1 are changed. The experimental groups are:
[0051] Group A: calcination temperature is 350℃ and holding time is 85min.
[0052] Group B: The roasting process includes a first insulation process at 350°C and a second insulation process at 500°C, wherein the insulation time of the first insulation process is 20 minutes; the insulation time of the second insulation process is 40 minutes.
[0053] The test was carried out according to the method of Example 1, and the results were:
[0054] Group A: The leaching rate of Li in step 2 was 99.0%. The Faraday efficiency of the magnetic separation material was as high as 82%, the H2O2 yield was 310 mmol g-1h-1, and the high H2O2 generation selectivity of more than 80% was maintained.
[0055] Group B: The leaching rate of Li in step 2 was 99.7%. The Radius efficiency of the magnetic separation material was as high as 92%, and the H2O2 yield was 336 mmol g-1h-1, maintaining a high H2O2 generation selectivity of more than 91%.
[0056] Comparative Example 1
[0057] Compared with Example 1, the only difference is that no siderite is added. Other operations and parameters are the same as in Example 1.
[0058] The leaching rate of Li in the leaching solution was 32.4%. The transition metal in the positive electrode was basically not recovered by magnetic separation (the recovery rate of transition metal was below 3%).
[0059] Comparative Example 2
[0060] Compared with Example 1, the only difference is that the siderite is replaced by MgCO3, and the other operations and parameters are the same as Example 1.
[0061] The leaching rate of Li in the leaching solution was 30.4%. The transition metal in the positive electrode was basically not recovered by magnetic separation (the recovery rate of transition metal was below 3%).
[0062] Comparative Example 3
[0063] Compared with Example 1, the only difference is that FeO is used to replace the siderite, wherein the amount of iron element is the same, and other operations and parameters are the same as Example 1.
[0064] The leaching rate of Li in the leaching solution was 69.8%. The transition metal in the positive electrode was basically not recovered by magnetic separation (the recovery rate of transition metal was below 3%).
Claims
1. A method for recovering waste lithium-ion battery positive electrode materials using siderite, characterized in that: The waste positive electrode materials stripped from waste lithium-ion batteries are mixed with siderite and transformed at a temperature of 300 to 700°C, followed by water immersion to obtain lithium liquid and transformation slag.
2. The method for recovering waste lithium-ion battery positive electrode materials using siderite as an auxiliary material according to claim 1, characterized in that: The positive electrode active material contained in the waste positive electrode material is an oxidized lithium salt of at least one element of nickel, cobalt and manganese; preferably at least one of lithium cobaltate, lithium nickelate, nickel-cobalt binary material and nickel-cobalt-manganese ternary material; Preferably, a conductive agent is also allowed to exist in the waste positive electrode material; preferably, the conductive agent includes at least one of conductive carbon black, graphite, and graphene.
3. The method for recovering waste lithium-ion battery positive electrode materials using siderite as an auxiliary material according to claim 2, characterized in that: In the waste positive electrode material, the content of positive electrode active material is 70-90wt.%, and the content of conductive agent is 5-15wt.%.
4. The method for recovering waste lithium-ion battery positive electrode materials using siderite as an auxiliary material according to claim 1, characterized in that: The weight ratio of the waste positive electrode material to the siderite is 1:2-10, preferably 1:3-7.
5. The method for recovering waste lithium-ion battery positive electrode materials using siderite as an auxiliary method according to claim 1, characterized in that: The waste positive electrode material and siderite are heated to the transformation temperature in a protective atmosphere and then kept at the temperature for transformation; Preferably, the protective atmosphere is at least one of nitrogen and an inert gas.
6. The method for recovering waste lithium-ion battery positive electrode materials with the aid of siderite according to claim 1, characterized in that: The transformation process includes a first heat preservation process at a temperature of 300 to 400°C and a second heat preservation process at a temperature of 500 to 600°C.
7. The method for recovering waste lithium-ion battery positive electrode materials using siderite as an auxiliary method according to claim 1, characterized in that: The holding time at the transition temperature is 30 to 90 minutes.
8. The method for recovering waste lithium-ion battery positive electrode materials using siderite as an aid according to claim 1, characterized in that: The liquid-to-solid ratio in the water immersion stage is 5-30 ml / g; Preferably, the hydrolysis temperature is 15 to 45°C; Preferably, the immersion time is 0.5 to 3 hours.
9. The method for recovering waste lithium-ion battery positive electrode materials using siderite as an aid according to any one of claims 1 to 8, characterized in that: The water-leached slag is subjected to magnetic separation treatment to obtain magnetic separation material and magnetic separation slag; the magnetic separation material is used as a catalyst for electrocatalytic hydrogen production.
10. The method for recovering waste lithium-ion battery positive electrode materials using siderite as an aid according to claim 9, characterized in that: More than 95% of the iron in the magnetic separation slag is in the form of α-Fe2O3.
Citation Information
Patent Citations
FeS2-assisted spheroidizing-oxidizing roasting lithium extraction method of waste positive electrode material
CN115652082A
Synchronous recovery process for lithium, manganese, nickel and cobalt in waste ternary lithium battery positive electrode material
CN116970811A
Method for recycling waste ternary lithium ion battery
CN117613438A
Cited By
Method for preparing battery-grade ferrous dihydrogen phosphate liquid through co-impregnation of ferrophosphorus slag and siderite and recovering copper / graphite
CN120328549A